2003
DOI: 10.1300/j033v10n03_02
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Characteristics as Moderators of the Satisfaction-Loyalty Link: Findings in a Business-to-Business Context

Abstract: Weitere Arbeitspapiere finden Sie auf unserer Internet-Seite: www.imu-mannheim.de 2 Our paper is organized as follows. We begin with a brief overview of the theoretical and conceptual background of our study and provide a synthesis of the extant empirical literature on the relationship between customer satisfaction and customer loyalty. We discuss relationship characteristics as possible moderators of this link and develop research hypotheses. Next, we discuss the method employed to test these hypotheses and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 69 publications
(67 reference statements)
7
90
1
Order By: Relevance
“…Moderating analyses were conducted to test hypotheses H3, H4 and H5 using the multi-group analysis function of AMOS in order to examine invariance between two samples (Steenkamp and Baumgartner, 1998). As Durvasula et al (1993) and Homburg et al (2003) suggested, we conducted a median split to divide the sample into two groups, one with high and one with low market dynamism. Next, we calculated a free model in which all parameters were estimated separately for the two samples and then compared this model to a model in which one of the structural paths was constrained to be equal in both samples (Thelen and Honeycutt, 2004).…”
Section: Hypotheses Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderating analyses were conducted to test hypotheses H3, H4 and H5 using the multi-group analysis function of AMOS in order to examine invariance between two samples (Steenkamp and Baumgartner, 1998). As Durvasula et al (1993) and Homburg et al (2003) suggested, we conducted a median split to divide the sample into two groups, one with high and one with low market dynamism. Next, we calculated a free model in which all parameters were estimated separately for the two samples and then compared this model to a model in which one of the structural paths was constrained to be equal in both samples (Thelen and Honeycutt, 2004).…”
Section: Hypotheses Test Resultsmentioning
confidence: 99%
“…The measurement models of proactive cost improvement and proactive performance improvement are both based on the proactive improvement scale by Deepen et al (2008), differing from that scale only in that the items of the Deepen et al scale refer to improvements in general, while our cost scale makes specific reference to improvements to increase cost efficiency and to reduce costs, and our performance scale makes specific reference to improvements to increase effectiveness and enhance the performance of the customer's logistics system. The measurement of retention and extension as the first two customer loyalty dimensions is based on the EJM 45,3 scales of Homburg et al (2003) and Cahill (2006). The retention indicators measure the customers' attitudes towards their LSPs with regard to repeat purchase intentions.…”
Section: Measurement Scalesmentioning
confidence: 99%
“…Face validity of the measurement items was assessed by conducting pretest interviews Homburg et al (2003), and Cahill (2006). For retention, indicators measure customers' attitudes towards their most important LSP with regard to repeat purchasing intentions of the same service.…”
Section: Measurement Model Assessmentmentioning
confidence: 99%
“…Tsai and Chen (2008) mentioned that in the Asian context key account management literature are very rare. Researches relating to key account management were conducted in western and other developed countries like South African perspective (Abratt and Kelly 2002), perspective of United States (Boles et al 1999), Germany context (Homburg et al 2002;Homburg et al 2003), context of The Netherlands (Kempeners and van der Hart 1999); from the perspective of United Kingdom (Millman and Wilson 1999); from Finland context (Ojasalo 2001), a French perspective (Pardo 1999); and from the context of Australian (Spencer 1999).…”
Section: Introductionmentioning
confidence: 99%